Índice de salubridade ambiental em áreas de interesse social: análise direcionada ao conjunto habitacional eldorado, Natal/RN - Almeida, Érika Laíze Silva (Universidade Federal Rural do Semi-Árido, 2021)
The disorderly growth of the population has generated numerous environmental impacts, motivated by deforestation, solid waste production and the growth of industrial activities. Most of these problems are caused by the lack of basic sanitation, resulting in low quality of life for the population, in addition to numerous diseases Therefore, the present research aimed to objective of evaluating the conditions of environmental health in an area of urban social interest in the city of Natal / RN. For this purpose, this assessment was carried out based on information relating to basic sanitation infrastructure, socioeconomic and housing conditions, which allowed the calculation of the environmental health index (ISA) for the Eldorado housing complex. The set could be classified as of medium healthiness, indicating the need for investments to achieve a healthy environment. At the end of the study, it was possible to conclude that the methodology used can be used as an instrument for planning and public management, analysis of the environmental situation of a given area and as a way to define the prioritization of investments.
Keywords: Saneamento; Meio Ambiente; Saúde; Sanitation; Environment; Health; ENGENHARIAS::ENGENHARIA CIVIL